Bacterial–fungal interactions and response to heavy metal contamination of soil in agricultural areas - Li, Jia; Zheng, Qiwen; Liu, Jiangyun; Pei, Shuwei; Yang, Zhen; Chen, Rentong; Ma, Li; Niu, Jingping; Tian, Tian (Frontiers in Microbiology, 2024)
Long-term heavy metal contamination of soil affects the structure and function of microbial communities. Here, we characterized the variations of microbial communities with soil heavy metal concentrations at Gansu Province, northwestern China. The pollution load index (PLI) was 1.05 and 0.14 for heavy metal contaminated area and uncontaminated area, respectively. PLI < 1 indicates that there is no pollution in the area, 1 < PLI < 2 is a depiction of moderate pollution. Cd, Hg, Pb, Zn and Cu were identified as the major contaminants in contaminated area, with the contamination factors were 30.35, 11.26, 5.46, 5.19 and 2.46, respectively. Heavy metal levels played a crucial role in shaping the difference of microbial community compositions. The diversities and compositions of bacterial community varied significantly between the two groups. Furthermore, the co-occurrence network between bacterial and fungal species in contaminated area was more complex, suggested that microorganisms adapt to long-term and moderate levels of heavy metal contamination through enhanced interactions. The keystone taxa of the co-occurrence network in contaminated area were more than uncontaminated area and completely different from it. Bacteria resistant to heavy metals may play an important role in soils contaminated with moderate levels of heavy metals over long periods of time. Analysis of the bacterial-fungal interactions in the presence of heavy metals could provide fundamental information for developing bioremediation mechanisms for the recovery of heavy metal contaminated soil.